Nutritional Assessment of Under Five Children Attending Pediatric Clinic in a Tertiary Care Hospital in the Capital of Nepal - Chhetri, Uma Devi; Sayami, Sujan; Mainali, Prabha (Journal of Lumbini Medical College, 2017)
Introduction: There has been a decreasing trend in malnutrition (stunting, wasting, and under-weight) in Nepal from 2001 till 2016 according to Nepal demographic health survey 2016. We tried to study whether these national survey data equally reflect the nutritional status of children visiting hospitals in the capital city of our country. The objective of the study was to evaluate the nutritional status of children less than five years of age brought to a hospital in Kathmandu. Methods: Anthropometric measurements (height/length and weight), other demographic details, and morbidity of all children, six months to five years of age, visiting the hospital over the period of three months were collected from the out-patient register. Height-for-age, weight-for-height, and weight-for-age were calculated and expressed as standard deviation units as compared to the median of reference data taken from WHO Multicentre Growth Reference Study Group (2007). Association between morbidity and various anthropometric values were calculated. Results: A total of 424 children were included in the study. There were 2.1% severely stunted, 8% stunted, 2.8% tall, and 1.7% very tall children. Similarly, 6.4% were severely wasted, 14.4% wasted, 4.7% severely under-weight, and 12.3% under-weight. The anthropometric values were significantly associated with morbidity (acute Vs chronic) but not associated with whether they were from within Kathmandu or form outside, and individual morbidity. Conclusion: Wasting and severe wasting in under five children from and nearby Kathmandu of Nepal is higher while stunting and severe stunting is lower as compared to previous National reports.